Pomalidomide in combination with dexamethasone results in synergistic anti‐tumour responses in pre‐clinical models of lenalidomide‐resistant multiple myeloma. (23rd February 2016) - Rychak, Emily; Mendy, Derek; Shi, Tao; Ning, Yuhong; Leisten, Jim; Lu, Ling; Miller, Karen; Narla, Rama K.; Orlowski, Robert Z.; Raymon, Heather K.; Bjorklund, Chad C.; Thakurta, Anjan; et al.
Summary: Pomalidomide is an IMiD ® immunomodulatory agent, which has shown clinically significant benefits in relapsed and/or refractory multiple myeloma (rrMM) patients when combined with dexamethasone, regardless of refractory status to lenalidomide or bortezomib. (Schey et al, 2004 ; San Miguel et al, 2013; Richardson et al, 2014; Scott, 2014 ) In this work, we present preclinical data showing that the combination of pomalidomide with dexamethasone (PomDex) demonstrates potent anti‐proliferative and pro‐apoptotic activity in both lenalidomide‐sensitive and lenalidomide‐resistant MM cell lines. PomDex also synergistically inhibited tumour growth compared with single‐agent treatment in xenografts of lenalidomide‐resistant H929 R10‐1 cells. Typical hallmarks of IMiD compound activity, including IKZF3 (Aiolos) degradation, and the downregulation of interferon regulatory factor (IRF) 4 and MYC, seen in lenalidomide‐sensitive H929 MM cell lines, were also observed in PomDex‐treated lenalidomide‐resistant H929 MM cells. Remarkably, this resulted in strong, synergistic effects on the induction of apoptosis in both lenalidomide‐sensitive and resistant MM cells. Furthermore, gene expression profiling revealed a unique differential gene expression pattern in PomDex‐treated samples, highlighted by the modulation of pro‐apoptotic pathways in lenalidomide‐resistant cells. These results provide key insights into molecular mechanisms of PomDex in the lenalidomide‐resistant setting.